2017
DOI: 10.1016/j.ijppaw.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Italian wolves ( Canis lupus italicus Altobello, 1921) and molecular detection of taeniids in the Foreste Casentinesi National Park, Northern Italian Apennines

Abstract: After centuries of massive decline, the recovery of the wolf (Canis lupus italicus) in Italy is a typical conservation success story. To learn more about the possible role of parasites in the wolves' individual and population health and conservation we used non-invasive molecular approaches on fecal samples to identify individual wolves, pack membership, and the taeniids present, some of which are zoonotic. A total of 130 specimens belonging to 54 wolves from eight packs were collected and examined. Taeniid eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
2
25
1
Order By: Relevance
“…To date, no information relating the prevalence of echinococcosis in sheep and cattle of the Park are available. However, the lower detection rate observed in this study, compared with what was reported by others (Gori et al 2015;Poglayen et al 2017), suggests a low prevalence of the parasite in livestock inhabiting the same area of the wolfs' pack. In addition, the wild boar, as a contamination source for echinococcosis in wild carnivores, could not be ruled out.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…To date, no information relating the prevalence of echinococcosis in sheep and cattle of the Park are available. However, the lower detection rate observed in this study, compared with what was reported by others (Gori et al 2015;Poglayen et al 2017), suggests a low prevalence of the parasite in livestock inhabiting the same area of the wolfs' pack. In addition, the wild boar, as a contamination source for echinococcosis in wild carnivores, could not be ruled out.…”
Section: Discussioncontrasting
confidence: 86%
“…As apex predator, wolves host a gastrointestinal parasite community that should vary in relation to the diet (Bryan et al 2012;Friesen and Roth 2016). Echinococcus granulosus sensu stricto (sheep strain genotype G1) is a common gastrointestinal parasite whose life cycle depends upon the predator-prey relationship (Friesen and Roth 2016) and it is an important emerging and reemerging zoonotic agent, above all in the Mediterranean basin (Poglayen et al 2017). Ungulates often comprise the majority of wolf diet (Meriggi et al 2011), but no wild cycle of E. granulosus has been described in Italy (Di Paolo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The differences of prevalence with respect to other Italian and European regions are likely to be modulated by the distribution and abundance of the local intermediate hosts (57,58). Taenia krabbei represents an exception, since it is reported in the artic fox (57,59) but rarely in the red fox (60) and it is more common in wolves, Italy included (24,61,62). Very recently, cisticercosis due to T. krabbei has been identi ed for the rst time in Italy in two hunted roe deer (Capreolus capreolus) and a dog of the Italian northern Apennines (63).…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that a single taeniid egg (T. hydatigena) contains around 7000 mitochondrial targets, and the detection limit of PCRs targeting the mitochondrial DNA was estimated at 33 copies [10•]. In our lab, a reliable method combining sieving (eggs retained in a 20-μm sieve), microscopy, multiplex PCR on DNA from taeniid-positive samples (egg-DNA PCR) and optionally confirmatory sequencing was developed [10•, 51] aiming to differentiate eggs of E. granulosus s.l., E. multilocularis and other taeniids, and the method has extensively been used for individual diagnosis (e.g., [54,60,61]) and in studies investigating field-collected specimens (see below). However, molecular analyses of taeniid eggs can also be performed after isolation with classical diagnostic sedimentation/flotation procedures [62,63].…”
Section: Diagnosis Of Intestinal Taeniid Infections By Fecal Examinationmentioning
confidence: 99%